Maternal grandmothers with advanced age reproduction are more likely to have Down syndrome grandchildren - Malini, Suttur S; Savitha, Mysore R; Ramachandra, Nallur B (Archives of Advances in Biosciences, 2011)
Down syndrome (DS), trisomy 21, is the most common chromosomal syndrome that affects one in 600-800 live births. The advanced maternal age is the only well known risk factor to cause DS. Our study revealed that many young mothers produced DS children than advanced age mothers in India. A total of 150 suspected DS cases were investigated cytogenetically. Randomly selected 200 healthy families in South India were used as controls. Logistic regression was performed on case-control dataset which was generated by randomly selecting the child from each of the control families. Pedigree analyses indicated that the maternal grandmothers had advanced age during conception of their daughters who gave birth to DS child. Case-control status was used as dependent variable, whereas parental and grandparental age was used as covariates. Logistic regression was reported as odds ratios, univariate and multivariate. The age of maternal grandmother showed highly significant difference in odds ratio, indicating that the advanced age of maternal grandmother was the possible risk factor. Therefore, it is important to sort-out the effect of advanced age mothers vs grandmothers on increased frequency of DS reported in different populations.